Kebijakan Harga dan Kebijakan Distribusi dalam Meningkatkan Daya Saing Industri Urea - Subhan, .; Sumarwan, Ujang; Daryanto, Arief; Kirbrandoko, . (Jurnal Aplikasi Manajemen, 2016)
Abstract: Urea is a chemical compound which is composed from the elements of carbon, hydrogen,oxygenand nitrogen. Approximately 90% of the urea used as chemical fertilizers in the form of prills as a supplier of nitrogen element (macro nutrient) needed by the plants. Fertilizer includes in the manufacturing industry that provides a major contribution to Gross Domestic Product (PDB) after the agriculture, Forestry, Fisheries, and mining sector (BPS, 2012). In the group of non oil and gas,fertilizer industry group is rank1 of 9 industry groups which have the opportunity to generate foreign exchange.The problems faced by the fertilizer industry in Indonesia are: (1) the availability of raw materials for producing urea namely natural gas, (2) the factory has been an old age and the old technology so that inefficient, (3) very low domestic sales policycauses the loss of opportunities for manufacturers to get the maximum margin. This study aims to analyze the factors influencing the income and profit in increasing the competitiveness of urea industry. The research to determine the relationship of competitiveness and the factors thataffectcompetitiveness is analyzed with multiple linear regression with the method of Ordinary Least Squared (OLS). As the independentÂ  variable it is the price policy (domestic price and export price) and the distribution policy (production volume and export volume) and the dependent variable are the competitiveness and the results of sales as the intervening variable. The data use in this research is secondary datacoming from the annual report of PT Pupuk Indonesia (Persero) and Urea Outlook from Fertecon Analysis. The results showed that the price policy (domestic price and exportÂ  price) and the distribution policy (production volume and export volume) are significantly influences toward the income and the profit that will increase and stregthen the company's competitiveness. For the domestic price variables did not significantly affect the results of sales(income) so that the policy of domestic price regulation is the same as the export price that will increase the income and the competitiveness of company. While the production volume and the export volume inflluence the results of sales so that it strengthens the competitiveness of company.